A review of high‐velocity impact on fiber‐reinforced textile composites: Potential for aero engine applications. Issue 1 (2nd April 2022) - Li, Yinghong; Chen, Xuefeng; Zhou, Jin; Liu, Xiaochuan; Zhang, Di; Du, Feiping; He, Weifeng; Jia, Pu; Liu, Haibao
Abstract: Considerable research has indicated that fiber‐reinforced textile composites are significantly beneficial to the aerospace industry, especially aero engines, due to their high specific strength, specific stiffness, corrosion resistance, and fatigue resistance. However, damage caused by high‐velocity impacts is a critical limitation factor in a wide range of applications. This paper presents an overview of the development, material characterizations, and applications of fiber‐reinforced textile composites for aero engines. These textile composites are classified into four categories including two‐dimensional (2D) woven composites, 2D braided composites, 3D woven composites, and 3D braided composites. The complex damage mechanisms of these composite materials due to high‐velocity impacts are discussed in detail as well.